2019
DOI: 10.1080/01425692.2018.1554474
|View full text |Cite
|
Sign up to set email alerts
|

The pedagogical logics of arts-rich schools: a Bourdieusian analysis

Abstract: The arts are under threat in English schools. But some schools and teachers work against the trend. To understand how they continue to offer rich arts experiences to students, we bring Bourdieusian thinking to arts teacher practices that were common across the thirty secondary schools we studied for three years. In addition to a flexible approach to the curriculum which encouraged independence, intellectual challenge and risk -taking, teachers also engaged in arts brokerageembodiment of arts engagement, ensuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Bourdieu and Passeron 1979). Indeed, even from within Bourdieu's own conceptual framework, "change in a field is not only possible but inevitable" and "even though fields are reproductive, they are not uniform" (Thomson et al 2019). As Gramsci (1973)…”
Section: Discussionmentioning
confidence: 99%
“…Bourdieu and Passeron 1979). Indeed, even from within Bourdieu's own conceptual framework, "change in a field is not only possible but inevitable" and "even though fields are reproductive, they are not uniform" (Thomson et al 2019). As Gramsci (1973)…”
Section: Discussionmentioning
confidence: 99%
“…The flexibility of the arts programme meant that the facilitators could avoid the re-creation of ‘schooled subjects’ and ‘schooled docility’ (Gallacher and Gallagher, 2008: 506) and they reported that developing supportive non-hierarchical relationships and emotional connections within the group helped the young people to feel secure. As in Thomson et al.’s (2019: 247) study with teachers, the facilitators could also be positioned as ‘arts brokers’, as they ‘embodied what it means to be culturally engaged’ and situated creativity as integral to everyday life, actively communicating this centrality to young people.…”
Section: ‘Breaking Free’: Reflections On the Value Of Engagementmentioning
confidence: 99%
“…Some art teachers also see that art practice means wider social and political questioning and engagement. These 'arts broker' teachers bring their own cultural participation and engagement to their work, demonstrating what it means for art practice to be an integral part of everyday life (Thomson et al 2019a). However, it is the commitment to the potential for everyone to have an idea, and realise it, that provides the moral foundation for the organisational and epistemological/methodological basis of the signature pedagogy creative project and contributes to the aesthetics and relationalities of art room atmosphere.…”
Section: (C) Implicit Valuesmentioning
confidence: 99%